Intensive care units nurses' burnout, organizational commitment, turnover intention and hospital workplace violence: A cross‐sectional study. Issue 2 (20th September 2022) - Wang, Tiemei; Abrantes, António Cunha Meneses; Liu, Yan
Abstract: Aims: This study aimed to (1) assess the relationship between intensive care unit (ICU) nurses' burnout, organizational commitment and turnover intention, (2) examine the moderating effect of the organizational commitment on the relationship between ICU nurses' burnout and turnover intention, and (3) explore the prevalence and influencing factors of hospital workplace violence among ICU nurses. Design: Cross‐sectional study design. Methods: Data were collected from August to October 2020 and a convenience sample of registered nurses was recruited. To control common method biases, one‐month temporal separation, Harman's single‐factor analysis and method of latent variables were adopted. The moderating effect was tested by SPSS Hayes PROCESS Macro. Chi‐square and logistic regression were used to examine workplace violence data. Results: Organizational commitment ( β = −.23, 95% confidence interval −.45 to −.03) and continuance commitment ( β = −.15, 95% confidence interval −.24 to −.16) have negative moderation effects on the relationship between emotional exhaustion and turnover intention. 77.7% of ICU nurses experienced workplace violence, male and staff nurses, and nurses with lower professional titles and shorter working years have greater odds of experiencing this violence.